THE UTILIZATION OF A NEUROLINGUISTIC APPROACH TO STUDENTS FOR ARABIC LANGUAGE LEARNING DEVELOPMENT - Mohammad Jailani; Suyadi Suyadi; Hendro Widodo (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
This study aimed to analyze Arabic language learning with a neurolinguistic approach at SMK Muhammadiyah 3 Yogyakarta. Students have not been able to accept the material presented by the teacher. Students have not responded with their brain intelligence, both in understanding mufradât as well as understanding muhâdatsah. This research used a case study approach, involving the principal, the representative of Ismuba (al-Islam, Kemuhammadiyahan, and Arabic Language) and the Arabic language teacher. Data were collected by observation and in-depth interviews. The results of the study prove that the neurolinguistic approach can understand students in mastering Arabic learning through brain synchronization, both right brain, and left brain. Optimizing Arabic language skills rests on his brain. This neurolinguistic approach can facilitate students in mastering istimâ', kalâm, qirâ'ah, and kitâbah abilities in Arabic learning.